Themes of polemical theology across early modern literary genres - Zavarský, Svorad (Cambridge Scholars Publishing, 2016)
This innovative volume spans the early modern period and ranges across literary genres, confessional divides and European borders. It brings together twenty-three scholars from thirteen different countries to explore the dynamic and profound ways in which polemical theology, its discourses and codes, interacted with non-theological literary genres in this era. Offering depth as well as breadth, the contributions chart a myriad of intersections between Catholic, Orthodox, Lutheran and Reformed polemics and a range of literary types composed in Latin and the vernacular across Europe. Individual essays discuss how genres such as history and poetry often represented a vehicle to promote and validate a particular confessional standpoint. Authors also address the complex relationship between humanism and polemical theology which tends to be radically oversimplified in early modern studies. A number of essays demonstrate the extent to which certain literary productions harnessed religious polemics in order to induce conversion or promote toleration, and might even engage with supranational issues, such as the divide between Eastern and Western churches. As such, this visionary book constructively bridges the world of religious controversy and the literary space.